2010
DOI: 10.1063/1.3391351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric field on low temperature multisubband electron mobility in a coupled Ga0.5In0.5P/GaAs quantum well structure

Abstract: The effect of uniform electric field on low temperature ͑T=0 K͒ multisubband electron mobility i is analyzed by considering a barrier delta-doped Ga 0.5 In 0.5 P / GaAs coupled double quantum well structure. We consider ionized impurity scattering and interface roughness ͑IR͒ scattering. The screening of the scattering potentials is obtained by adopting the random phase approximation. Starting with a double-subband occupied system we have studied the changes in the intrasubband and intersubband scattering proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The Hartree potential is obtained from the Poisson's equation by using a variational approach. 11,15,21 We use multistep potential approximation to calculate the transmission coefficient across the potential V (z) from which E n and ψ n (z) can be obtained as a function of F. 11,15,22 A diagram illustrating the effect of the external electric field F on the potential structure, subband energy levels and wave functions of a single side barrier delta doped double quantum well structure is presented in Fig. 1.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The Hartree potential is obtained from the Poisson's equation by using a variational approach. 11,15,21 We use multistep potential approximation to calculate the transmission coefficient across the potential V (z) from which E n and ψ n (z) can be obtained as a function of F. 11,15,22 A diagram illustrating the effect of the external electric field F on the potential structure, subband energy levels and wave functions of a single side barrier delta doped double quantum well structure is presented in Fig. 1.…”
Section: Theorymentioning
confidence: 99%
“…13,21 Starting from Boltzmann transport equation, 21 the electron subband transport lifetime τ 0 and τ 1 of a double subband occupied structure can be expressed as 1/τ 0 = (A 00 A 11 -A 01 A 10 )/(A 11 -A 01 ) and 1/τ 1 = (A 00 A 11 -A 01 A 10 )/(A 00 -A 10 ), where A 00 =B 00 +C 01 , 10 , A 11 =B 11 +C 10 and k F n =(2mE F n / 2 ) 1/2 . B nn are intrasubband scattering rate matrix elements and C nm and D nm are intersubband scattering rate matrix elements, 11,15 which can be written in terms of screened scattering potentials V eff nm (q nm ) as: 11,15 …”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,6 When more than one subband is occupied, the mobility is considerably influenced by the intersubband effects exhibiting nonmonotonic behavior. [17][18][19][20][21][22][23][24] We note that even though a number of works have been done on the electron mobility in different quantum wells, the study of multisubband electron mobility near resonance of subbands due to variation of structure parameters of a double quantum well has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…15 Several works have also been done on the study of the effect of external electric field on the enhancement of electron mobility in quantum well systems. [16][17][18][19] It has been shown that the application of external electric field leads to nonmonotonic oscillating electron mobility mediated by intersubband effects. 18,19 Attempts have also been made to study the electron mobility as functions of the structure parameters such as doping concentrations, well widths and barrier widths of different quantum wells.…”
Section: Introductionmentioning
confidence: 99%